Pengaruh Metode Inkuiri Terbimbing terhadap Hasil Belajar IPA pada Peserta Didik Kelas V SD Negeri 060837 Medan (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to highlight the effectiveness of the Directed Research Method in science classes highlighting Heat Transfer and Its Benefits in Daily Life for fifth-grade students at SD Negeri 060837 Medan. Considering the use of quantitative data, this study falls into the quantitative research category. The approach used is a quasi-experimental method, characterized by changing standard conditions to specific conditions, while monitoring and regulating external factors that may affect the research results. The study design involved two classes that received different treatments. A striking difference was seen in the science learning achievement of students taught with the Directed Research Method compared to those who did not receive the intervention. This was reflected in the average post-test results reaching 75.2 for students who learned using the Directed Research Method, while the average post-test results for students taught with the traditional method were 74.2. These findings indicate that students who participated in learning through the Directed Research Method obtained higher average scores in science lessons compared to those who did not receive the treatment. This test was applied to test the hypothesis. The t-test analysis of the learning outcomes of both classes showed a t-test value that exceeded the t-table value, namely 4.46 compared to 1.669. The acceptance of Ha shows that the Directed Research Method successfully supports the teaching of Heat Transfer and Its Benefits in Daily Life to fifth-grade students at SD Negeri 060837 Medan in the 2024/2025 academic year. Therefore, it can be concluded that the Directed Research Method has a significant influence on science lessons that discuss Heat Transfer and Its Benefits in Daily Life.